The rise of China and its implications for emerging markets: Evidence from a GVAR model - Martin Feldkircher; Iikka Korhonen (Bank of Finland, Institute for Economies in Transition (BOFIT), 2012)
This paper studies empirically the role of China in the world economy. We examine both the way the Chinese economy reacts to selected exogenous macroeconomic shocks and the repercussions for the world economy of a shock emanating from China. With regard to the latter, we focus on the responses of emerging markets, in particular those in Europe. Based on a global VAR (GVAR) model and a new data set that excels in country coverage and covers the most recent time period including the global financial crisis, our results are threefold: First, we show that a +1% shock to Chinese output translates to a permanent increase of 1.2% in Chinese real GDP and a 0.1% to 0.5% rise in output for most large economies. The countries of Central Eastern Europe (CEE) and the former Commonwealth of Independent States (CIS) also experience an output rise of 0.2%, while countries in South-Eastern Europe see a permanent 0.1% reduction in output. Secondly, to benchmark the shock to Chinese output, we examine the response to a +1% shock to US GDP. The results show that the US economy remains dominant in the world economy despite the rapid rise of China in recent years. In this vein, output rises in advanced economies by 1% to 1.4% and in the CIS and CEE regions by 1.5% and 0.7% respectively. By contrast China seems to be little affected by the US shock. Finally, we examine the effect of a +50% hike in oil prices on China and emerging economies. As one of the largest oil exporters, Russia's real output increases by about 6%. In contrast, the surge in oil prices puts a drag on Chinese output, amounting to 4.5% in the long-run.
URN:NBN:fi:bof-201408072169
Keywords: C32; F44; E32; O54; 330; China; macroeconomic shocks; foreign shock; GVAR; great recession